The influence of relational orientation on Chinese consumers' responses towards apparel mass customisation. (11th October 2011) - Song, Shawn Kun; Fiore, Ann Marie
This study examined the impact of a Chinese cultural value, relational orientation, on Chinese consumers' responses towards mass customisation of apparel. Relational orientation, which stresses the conformity to group norms, was found to moderate the relationships between mass customisation and several aspects of consumers' perceived value. Specifically, relational orientation negatively affected perceived economic value and enjoyment from apparel mass customisation by Chinese consumers. It also negatively affected the impact of several aspects of perceived value on consumers' behavioural intention towards a marketer. The research suggests the need for differentiated marketing strategies based on consumers' relational orientation when implementing mass customisation of apparel in the People's Republic of China.